THE DEVELOPMENT OF THE COORDINATIVE CAPACITY BY USING GYMNASTICS MEANS - Lidia Petrache; Florian Benedek (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In the present paper it's approached the use of gymnastics methods for the development of the coordinative capacity. I chose this paper because it presents an interest regarding the following aspects: the movement game, gymnastic free exercises and the exercises with portable objects for children; all these being also attractive and they succeed involving them in different activities.